The Impact of a Nationwide Antibiotic Restriction Program on Antibiotic Usage and Resistance against Nosocomial Pathogens in Turkey - (:unkn) unknown (IVYSPRING INT PUBL, 2011)
Purpose: Antimicrobial resistance among microorganisms is a global concern. In 2003, a nationwide antibiotic restriction program (NARP) was released in Turkey. In this study we evaluated the effect of NARP on antibiotic consumption, antimicrobial resistance, and cost. Materials and Methods: The data obtained from all of the four university hospitals, and one referral tertiary-care educational state hospital in Ankara. Antimicrobial resistance profiles of 14,233 selected microorganisms all grown in blood cultures and antibiotic consumption from 2001 to 2005 were analyzed retrospectively. Results: A negative correlation was observed between the ceftriaxone consumption and the prevalence of ceftriaxone resistant E. coli and Klebsiella spp. (rho:-0.395, p:0.332 and rho:-0.627, p:0.037, respectively). The decreased usage of carbapenems was correlated with decreased carbapenems-resistant Pseudomonas spp. and Acinetobacter spp (rho:0.155, p:0.712 and rho:0.180, p:0.668, respectively for imipenem). Methicillin resistance rates of S. aureus were decreased from 44% to 41%. After two years of NARP 5,389,155.82 USD saving occurred. Conclusion: NARP is effective in lowering the costs and antibiotic resistance.
Keywords: Antibiotic consumption; antimicrobial resistance surveillance; restriction policy; INTERVENTION PROGRAM; ESCHERICHIA-COLI; COST SAVINGS; POLICY; CONSUMPTION; CEPHALOSPORINS; FORMULARY